2019
DOI: 10.1039/c9fo00766k
|View full text |Cite
|
Sign up to set email alerts
|

Dietary methionine restriction improves the gut microbiota and reduces intestinal permeability and inflammation in high-fat-fed mice

Abstract: Dietary methionine restriction improved the intestinal microbiota composition, barrier function, oxidative stress, and inflammation in high-fat-fed mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 68 publications
4
80
1
Order By: Relevance
“…SCFAs play an important role in maintaining the integrity of the intestinal epithelial barrier by regulating tight junction proteins. 29,30 As expected, we found that NLRP3 deficiency compensates for gut barrier destruction induced by AP, as revealed by increased expression of Claudin-1 and Occludin in NLRP3 KO mice with AP. Collectively, we speculate that the knockout of NLRP3 resists the gut microbial dysbiosis induced by AP, including the enrichment of beneficial bacterial and reduction of pathogenic bacterial, which partly contributes to the alleviation of systematic inflammation (Figure 8).…”
Section: Discussionsupporting
confidence: 83%
“…SCFAs play an important role in maintaining the integrity of the intestinal epithelial barrier by regulating tight junction proteins. 29,30 As expected, we found that NLRP3 deficiency compensates for gut barrier destruction induced by AP, as revealed by increased expression of Claudin-1 and Occludin in NLRP3 KO mice with AP. Collectively, we speculate that the knockout of NLRP3 resists the gut microbial dysbiosis induced by AP, including the enrichment of beneficial bacterial and reduction of pathogenic bacterial, which partly contributes to the alleviation of systematic inflammation (Figure 8).…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with these results, methionine biosynthesis was decreased in the post-Kasai group. Previous research has demonstrated that dietary methionine restriction improves the gut microbiota and reduces intestinal permeability and inflammation ( 27 ). We concluded that the gut microbiota, intestinal permeability, and inflammation were improved in the post-Kasai group.…”
Section: Discussionmentioning
confidence: 99%
“…Using chronic social defeat in male mice, we showed that some of the long-lasting bacterial changes in cecum contents were linked to severity of social avoidance (a behavioral feature reflective of susceptibility to the depressive-like effects of the stressor) and to brain pro-inflammatory cytokines ( Szyszkowicz et al., 2017 ). Although these observations were correlational, considering that the genera affected by the social stressor and correlated to behavioral and brain cytokine phenotypes ( Oscillospira and Parabacteroides ) have anti-inflammatory properties ( Koh et al., 2018 ; Yang et al., 2019 ), they suggest that severity of social avoidance in chronically defeated mice could be linked to an increased inflammatory tone along the gut microbiota-immune-brain axis. We confirmed this possibility by showing that male mice exposed to chronic social defeat had long-lasting elevations of the pro-inflammatory cytokines IL-1β and TNF-α in the middle section of the small intestine (jejunum), which were accompanied by abnormal expression of tight junction proteins (reflective of increased membrane permeability) ( Santos et al., 2021 ).…”
Section: The Gut Microbiota-immune-brain Axis and Depressive Illnessesmentioning
confidence: 94%